Diseño de un sistema productivo integral para la crianza y producción de animales menores usando terrenos con escasos servicios de regadío - Caizaluisa Quimbita, Stefany Jimena (2022)
The research project has as main aim to design a productive integral system for raising small animals by using land with few irrigation services, whose problem derives from an industrial process absence, what covers the water limited amount optimal use that exists into Culaguango Bajo neighborhood, for making good sowing, maintenance and harvesting practices of alfalfa, by improving soil moisture and pH, through an automatic sprinkler system developed onto the Arduino platform. The used methodology was descriptive with field, bibliographic, deductive and inductive methods. The results showed that, through five irrigations in one day, it is possible to increase the humidity to 2.12% and the pH to 6.52, by favoring a better alfalfa crop, which is reflected a more leaf stand. Among the conclusions, it is highlighted, what the generation an integral production program for feeding small animals, based on forage allowed getting fundamental procedures matrices for the rabbits and guinea pigs care and feeding, as well as, the sowing alfalfa maintenance; it reaches for improving the production breeding and production conditions, so rabbits and guinea pigs, through a more nutritious forages for the animals' diet; which is replicated into the inhabitants economic sustainability from Culaguango Bajo neighborhood, from Belisario Quevedo parish, who sustain their basic food basket exclusively from agriculture and the raising these domestic species.